THE INFLUENCE OF MENU DIVERSITY, PRICES, AND ISLAMIC BUSINESS ETHICS ON CONSUMER LOYALTY WITH SATISFACTION AS AN INTERVENING VARIABLE (Customer Study of Mr. H. Masyhudi's Young Kambing Sate Restaurant, Blotongan Salatiga) - Aslamiyah, Aslamiyah; Guritno, Agung (Sharia Business Management UIN Raden Intan Lampung, 2024)
The aim of this research is to determine the influence of menu diversity, prices and Islamic business ethics on consumer loyalty with satisfaction as an intervening variable. The type of research used in this research is quantitative research using primary data. Data collection uses direct methods, such as data obtained from the field or sources. The object of this research is at BPK's young goat satay restaurant. H. Masyhudi Blotongan, Salatiga. The population in this study were all buyers at the Mashhudi young goat satay restaurant. And the number of samples used is part of the population using purposive sampling techniques. The analysis technique used is a regression analysis technique which is processed using SPSS. The results of this research based on the t test show that menu diversity has an insignificant negative effect on satisfaction. Price has a significant positive effect on consumer satisfaction. Islamic business ethics has a significant positive effect on satisfaction. Satisfaction has a significant positive effect on loyalty. Menu diversity has an insignificant negative effect on loyalty. Price has an insignificant negative effect on consumer loyalty. Islamic business ethics has an insignificant negative effect on consumer loyalty. Menu diversity has an insignificant negative effect on loyalty with satisfaction as an intervening variable. Price has a significant positive effect on loyalty with satisfaction as an intervening variable. Islamic business ethics has a significant positive effect on loyalty through consumer satisfaction.